Analysis of mobilization elements in plasmids from Shigella flexneri. - Roessler, E (1985)
The mobilization properties of three plasmids were examined after cotransfer from Shigella flexneri to Escherichia coli. The largest plasmid, pCN1, was shown to be a conjugative R factor that could promote its own transfer and allow cotransfer of a 4.1-kilobase plasmid, pCN3; mobilization of the third plasmid, pCN2 (6.3 kilobases), required the presence of both pCN1 and pCN3. Sequences from pCN2 and pCN3 homologous to the bom (basis of mobilization) sites of ColE1 and pBR322 were localized by analysis of site-specific deletion derivatives generated in vivo during the transfer of composite plasmids and were characterized by DNA sequencing.